Improving Mathematical Creative Problem Solving Skill of Male and Female Students through Situation-Based Learning - Isrok’atun, Isrok’atun (Universitas Negeri Malang, 2017)
Abstract: The purpose of this research was to investigate the improvement of male and female students’ mathematical Creative Problem Solving (CPS) ability as a result of Situation-Based Learning. The quasi experimental design was used by involving two methods, namely Situation-Based Learning and conventional method. The population of the research was high school students in Central Java Province. The research instrument used in the study was CPS test. The data were analyzed based on the students’ gender. The research resulted in the following conclusions: (1) the improvement of students’ mathematical CPS ability taught under SBL was higher than those who were taught using conventional method based on students’ gender, and (2) there was no interaction between learning model and gender on the improvement of students’ mathematical CPS ability.Keywords: female students, improvement of mathematical CPS ability, male students, SBL learningAbstrak: Tujuan penelitian ini adalah untuk mengetahui peningkatan kemampuan CPS matematis siswa laki-laki dan perempuan sebagai akibat dari pembelajaran SBL. Penelitian kuasi eksperimen ini menerapkan dua model pembelajaran yaitu pembelajaran SBL dan pembelajaran konvensional. Populasi penelitian ini adalah siswa SMA di Provinsi Jawa Tengah. Instrumen penelitian yang digunakan yaitu tes kemampuan CPS matematis. Analisis data ditinjau berdasarkan gender siswa. Hasil penelitian menyimpulkan: 1) peningkatan kemampuan CPS matematis siswa yang mendapat pembelajaran SBL lebih baik daripada siswa yang mendapat pembelajaran konvensional ditinjau dari gender siswa; dan 2) tidak terdapat interaksi antara pembelajaran dan gender siswa terhadap peningkatan kemampuan CPS matematis.Kata Kunci: pembelajaran SBL, peningkatan kemampuan CPS matematis, siswa laki-laki, siswa perempuan